Linked Economic and Animal Systems (LEAS) model - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
The Linked Economic and Animal Systems (LEAS) model is a systems-based analytical approach linked with RIAPA through several handshake variables (price and quantities) depicting information flows both ways. The LEAS model was developed in response to major implications that emerge from the recent literature on livestock systems in developing countries, including the need for a livestock systems approach that accounts for the downstream linkages connecting producers and consumers, the reliance of the livestock sector development on the future trajectory of the broader economy, and the need for a holistic approach that helps prioritize livestock sector interventions. The LEAS model incorporates a well-disaggregated herd dynamics module (HDM) linked to RIAPA that in turn passes information to microsimulation modules that help trace changes in poverty, household consumption, and dietary diversity. The HDM is a lifecycle (stock-flow) module that tracks annual herd/flock size disaggregated by age, sex, breed/strain, and agroecology zone. It estimates reproduction, births, deaths, and offtakes (slaughtering) for different types of animals (such as cattle, chickens, sheep, and goats). Given information on consumer demand for animal products and the profitability of animal offtake activities, the HDM estimates offtake level, remaining herd size, and annual feed requirement. Several policy interventions are embedded within the HDM, such as public-provision of medicines to improve animal health or access to improved feed to increase on-farm livestock productivity. Environmental variables such as forage supply and biophysical carrying capacity are incorporated to capture the impact of climate on herd stock and productivity. The HDM also incorporates parameters and variables for analyzing shocks (drought, disease, etc.) to the livestock system. The HDM is currently calibrated for cattle, but can easily be adapted to study other livestock systems including small ruminants and poultry. The LEAS model has been used to assess the implications of national development scenarios on the livestock sector performance, and the response of cattle herds to weather shocks.